Only humans need apply: winners and losers in the age of smart machines - Davenport, Thomas H. (New York, 2016)
Nearly half of all working Americans could risk losing their jobs because of technology. It?s not only blue-collar jobs at stake. Millions of educated knowledge workers?writers, paralegals, assistants, medical technicians?are threatened by accelerating advances in artificial intelligence. The industrial revolution shifted workers from farms to factories. In the first era of automation, machines relieved humans of manually exhausting work. Today, Era Two of automation continues to wash across the entire services-based economy that has replaced jobs in agriculture and manufacturing. Era Three and the rise of AI, is dawning. Smart computers are demonstrating they are capable of making better decisions than humans. Brilliant technologies can now decide, learn, predict and even comprehend much faster and more accurately than the human brain and their progress is accelerating. Where will this leave lawyers, nurses, teachers and editors?
Keywords: Automation - Economic aspects